Pengaruh Metode Pembelajaran Question Student Have terhadap Hasil Belajar Siswa pada Mata Pelajaran Fiqih Kelas VII di Mts Al-Bukhary - Rieza Millatul Islamy; Achmad Fauzi (Jurnal Subulana, 2021)
This article aims to determine the effect of the Question Student Have learning method which is very helpful in improving the students' learning outcomes of Islamic Islamic Civilization History at MTs Al-Bukhary. This research is a quantitative research type Pre Experimental Design, the subject in this research is class VII MTs Al-Bukhary. The research sample was the control group using the lecture method and the experimental group using the Question Student Have learning method. Data analysis techniques used the normality test with Kormogolov followed by hypothesis testing with the t test. The results showed that the implementation of learning using the Question Student Have learning method was very helpful in improving the learning outcomes of students' Islamic Civilization History at MTs Al-Bukhary. Based on the results of the analysis and discussion of the research data, the results of the SPSS hypothesis test were obtained with tcount = -4.791> ttable = 1.70 as a result, Ho was rejected, based on these results that there was an effect of learning outcomes among students taught using the Question Student Have learning method compared with the lecture learning method. Students with learning treatment using the Question Student Have learning method, have better learning outcomes than students with the learning treatment of the lecture learning method.